Catholic schools as spaces for transformative encounter - Lamont, Tracey (2018)
The U.S. Conference of Catholic Bishops created a curriculum for Catholic secondary schools that describes what adolescents should learn including the importance of developing a religious and moral identity, encounters through service, and a deeper understanding of interreligious dialogue. This study adds the how to the bishops' what by exploring Blasi's theory of the moral self as it relates to Kegan's constructive-developmental theory to enable religious educators to create a transformative curriculum of encounter in Catholic secondary schools that helps adolescents develop habits of dialogue and a mature pluralism towards a sense of shared moral responsibility.